Effect of tartary buckwheat and highland barley flours on the quality of glutinous rice cakes determined by nutritional composition, physical structure, sensory perception and flavour. (7th March 2023) - Zhou, Mei; Li, Yanmi; Yuan, Ziqi; Luo, Liming; Ren, Yuanhang; Zeng, Qingchen; Qi, Anyin; Huang, Jingwei; Cao, Xiaoning; Shi, Zhiqiang; Wu, Xiaoyong; Wu, Qi; et al.
Summary: Tartary buckwheat flour, highland barley flour and glutinous rice flour were utilised as the raw materials to prepare coarse‐cereal glutinous rice cakes. Their quality was compared to that of traditional glutinous rice cakes (made with japonica and glutinous rice flours), based on nutritional composition, physical structure and flavour. The addition of tartary buckwheat and highland barley flours significantly increased the contents of protein, total flavonoids and β‐glucan ( P < 0.05). The tartary buckwheat flour gave the glutinous rice cakes a yellow‐green colour, and the coarse‐cereal glutinous rice cakes had better hardness and chewiness. Aldehydes, alcohols as well as ketones were the chief volatile flavour components of the coarse‐cereal glutinous rice cake. These coarse‐cereal glutinous rice cakes were more popular compared to the traditional glutinous rice cakes with evaluators on a sensory panel. This may give some guidance for the development of coarse‐cereal products, such as tartary buckwheat and highland barley. Abstract : Quality comparison between coarse‐cereal glutinous rice cake and traditional glutinous rice cake.